Reinforcing Social Interaction Among Persian Neighborhood Communities in New High-Rise Residential Development - Abbaszadeh, Shahab (2009)
Neighborhood communities are losing their social interactions when residences are stacked into high-rise residential buildings (HRBs) complexes in Mashhad metropolis, Iran. The houses would become mere physical shelters, hence lowering the quality of modern neighborhood communities. This study conducted a mixedmethod case study research in search for “How can architects adopt traditional Persian spatial principles of neighborhood communities in developing social interactions in neighborhood communities of HRBs complexes?” After a rigorous literature analysis, the study develops two theoretical propositions. The first posits that social interaction among residents will occur successfully when HRBs complex provides secured, supportive, collective, and responsive spaces for them. The second proposes that HRD (high-rise residential district) is a neighborhood community consisting of several HRBs that encourages social interactions through wellintegrated secured, supportive, collective and responsive spaces. The study utilizes mixed-method data collection to support the proposed propositions. It considers a HRBs complex in Mashhad as the qualitative unit of analysis while considering a family living in one apartment as the quantitative unit of analysis. Data were obtained from semi-structured interviews with selected experts, non-participant observation of three selected HRBs complexes, and survey of residents’ opinion. Validation of propositions is obtained using triangulation in data collection of qualitative part of the study and statistical analysis. Interview reveals that experts support the needs for secured, supportive, collective, and responsive spaces in improving the quality and quantity of open spaces in contemporary HRBs complexes. They also agreed to redefine the concept of current spaces to support residents’ socio-cultural behaviors. Field observations at the three selected residential complexes reveal that residents do not appreciate open spaces for the sake of having open spaces in their living area. They prefer to spend their time in better quality spaces even when that open space is further away from their residential complexes. Although this study have identified the four influential constructs in the establishment of social interaction in traditional Persian neighborhood communities—secured, supportive, collective, and responsive spaces—it also found differences in the level of priority of those constructs. Thereby, the study established HRD as a neighbourhood community consisting of several HRBs that encourages social interactions through well-integrated responsive, supportive and secured spaces in a collective context. It recommends architects to design hierarchical spaces at three territorial levels: single unit neighborhood community, a group of neighborhood territories, and a residential district. The study believes that these principles could promote unification of the neighborhood communities. In summary, the study contributes in developing social interaction as the contributing factor for maintaining values of traditional Persian neighbourhood communities in the design of HRBs complexes in Iran. It merges socio-cultural behavior in physical spatial features of the built environment for improving social interaction in non-western HRD developments. Moreover, it redefines Newman’s Defensible Space Theory on secured spaces where they are, in fact, the hierarchical spatial structure that provides security by increasing the sense of familiarity and responsibility among residents through informal interactions in Persian HRD. This study helps to sustain the indigenous socio-culture of a developing nation as its population and built environment evolve to follow western-inclined lifestyle.